Spillover effects of international standards: Work conditions in Vietnamese small and medium enterprises - Neda Trifković (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Most studies focus on trade effects and organizational outcomes of international standards, neglecting the effect of standards on employees. Using a two-year matched firm-employee panel dataset, this paper finds that the application of standards improves work conditions in small and medium enterprises in Vietnam. Certified firms pay higher wages on average. They are also more likely to offer formal contracts and to pay social and health insurance to workers. The estimation accounts for endogenous matching of workers with firms and unobserved heterogeneity using an instrumental variable approach. The study reveals unexpected benefits from certification, calling for higher investment in standards.
Keywords: D22; F16; J31; J81; O12; 330; international standards; work conditions; wages; SMEs; externalities; Vietnam